NILAI KEADILAN DALAM ETIKA PELAYANAN PUBLIK KONSEP DAN IMPLEMENTASINYA - Philipus, Ngorang (E-Journal Widya Yustisia, 2005)
Providing service to the people (public service) is a state officialâs duties. General image denotes low quality of public service, as seen in high corruption practice and national development discrepancy in regional, ethics and religion perspective. This research found out that these realities are due to the low level of salary and the will of state officials to increase their life standard by using their power and authority in the public office. Coping with this bad condition, it is necessary to build the internal and external control, to raise salary, to give protection to whistleblower, and to remember the rights and duties of state official. By doing so, justice value in public service ethics will be formed automatically